Design of power monitoring system for new energy grid-connected operation based on LoRa and 4G technology. (November 2022) - Wu, Zhongchao; Zhu, Mingxing; Li, Qi; Xue, Lijun; Yang, Jilian; Chen, Zhihui; Cao, Yanjun; Cui, Yan
Abstract: With the large-scale development and utilization of new energy, in order to achieve rapid collection, monitoring and judgment of grid-connected power quality data, this paper proposes a design scheme of a remote acquisition and monitoring system for power data based on LoRa and 4G communication technology. The system uses high-precision A/D to sample various types of electrical energy information such as current and voltage in real time, uses digital signal processor (DSP) chips to complete power quality data calculation, and combines LoRa, 4G and cloud platform technologies to achieve distributed remote metering and centralized monitoring. Experimental results show that the proposed scheme and the designed system have good tracking capability, and meet the requirements of technical specifications to calculate and analyze the conversion efficiency (>90%) and total harmonic distortion (<5%) of the grid-connected system, which improves the safety and monitoring efficiency of new energy power plants connected to the power grid.